Strategi Pemasaran Layanan Jasa Mobile Banking Bank 9 Jambi Syariah Kantor Cabang Muara Sabak - Erwina Kartika Devi; Bahrul Ma'ani; Husin Abdul Wahab (Jurnal Ilmiah Ekonomi Islam, 2023)
Bank 9 Jambi Syariah Muara Sabak Branch implements one of the most popular banks in the community. Mobile banking services allow customers to perform various transactions without the need for a banker, such as transferring money between accounts. The mobile banking services provided by Bank 9 Jambi are also owned by other banks, but the growth of customers owned by Bank 9 Jambi is quite significant. What is the Marketing Strategy for Mobile Banking Services at Bank 9 Jambi Syariah Muara Sabak Branch Office? Answering this question, the researcher uses a qualitative research approach. The sample used in this study was Bank 9 Jambi Muara Sabak branch located in Tanjung Jabung Timur. The analysis used in this research is descriptive qualitative analysis. The results of this study indicate that the marketing strategy of mobile banking services at Bank 9 Jambi aims to increase promotional activities, minimize tariff rates with optimal results, and a short registration process. The obstacle faced by Bank 9 Jambi Syariah Muara Sabak Branch Office in marketing mobile banking services lies in promotion. The promotion carried out by Bank 9 Jambi was not well received by rural communities due to lack of understanding of technology and lack of socialization.